Blinded by the Sunlight : Emerging from the Prison of Saddam's Iraq - McAllester, Matthew, 1969- (New York HarperCollins Publishers, 2004)
A Pulitzer Prize-winning journalist and Iraqi prison survivor shares the story of his incarceration and the obstacles that were overcome to secure his release, in a personal account that also gauges the prospects of Iraqis during and after Saddam Hussein's rule.
Include Colour Illustration
Keywords: United States -- Iraq -- Iraq War (2003-2011) -- Journalists -- McAllester, Matthew, 1969-